A path for diagnosis and therapy of colon cancer: a continuous quality improvement - Giuliani, Jacopo; Marzola, Marina (Chinese Journal of Cancer Research; Vol 26, No 6 (December 30, 2014): Chinese Journal of Cancer Research, 2014)
Objective: Prognosis of colorectal cancer strongly depends on stage at diagnosis, which can be cured in most cases at an early stage. The results were supported by different screening programmes. Few data concerning analysis of different phases of Colorectal Cancer Program were reported in literature. The aim of this study is to analyze “step by step”, from a longitudinal type, the Colorectal Cancer Program, active at our Institution, verifying compliance with standards of care. Methods: We compared two different populations during the same period: patients referring to our Clinical Oncology Unit coming from Regional Colorectal Cancer Screening Program and the other population that was not in any Colorectal Cancer Program. Results: Considering patients from the Regional Colorectal Cancer Screening Program (19 patients, corresponding to 24.0% of the general case study), 3 (15.8%) were deceased and 16 (84.2%) were alive without evidence of the disease (NED). Concerning patients that are not coming from Regional Colorectal Cancer Screening Program (61 patients, corresponding to 76.0% of the general case study), 9 (14.8%) were deceased, 43 (70.5%) were NED, 8 (13.1%) were alive with metastases and 1 (1.6%) was lost during follow-up (PFU). Conclusions: On the basis of this experience, we concluded for high-quality care for both populations. Any critical point should be carefully analyzed in order to implement quality of care.